Perturbation of Transmission Matrices in Nonlinear Random Media. Issue 9 (19th July 2019) - Fleming, Adam; Conti, Claudio; Di Falco, Andrea
Abstract: Random media with tailored optical properties are attracting burgeoning interest for applications in imaging, biophysics, energy, nanomedicine, spectroscopy, cryptography, and telecommunications. A key paradigm for devices based on this class of materials is the transmission matrix, the tensorial link between the input and the output signals, that describes in full their optical behavior. The transmission matrix has specific statistical properties, such as the existence of lossless channels, that can be used to transmit information, and are determined by the disorder distribution. In nonlinear materials, these channels may be modulated and the transmission matrix tuned accordingly. Here, the direct measurement of the nonlinear transmission matrix of complex materials is reported, exploiting the strong optothermal nonlinearity of scattering silica aerogel (SA). It is shown that the dephasing effects due to nonlinearity are both controllable and reversible, opening the road to applications based on the nonlinear response of random media. Abstract : A key paradigm for random media is the transmission matrix, the tensoral link between input and output signals, that describes their optical behavior. This work details the characterization of the transmission matrix in the nonlinear regime, through a pump–probe scheme with phase wavefront manipulation. Such a measurement paves the way for a new generation of nonlinear devices based on random media.